Analisa Kadar Protein Total Ikan Kurisi (Nemipterus japonicus) Segar yang Diawetkan dengan Biji picung Tua (Pangium edule Reinw) - Hidayati, Arini; Santoso, Hari; Syauqi, Ahmad (Jurnal SAINS ALAMI (Known Nature), 2020)
Curry fish catch by fishermen is quite abundant, kurisi fish contains protein between 5-20%, and fat is about 5% and is easy to lime (rot). Kurisi fish are utilized by fishing communities in the form of processed surimi and dried fish (salted fish). One alternative is the inhibitor of the decay process with preservation using old picung seeds (Pangium edule Reinw). The purpose of this study was to analyze the levels of preserved curry fish protein using old picung seeds. The research method was carried out experimentally using a factorial design, namely Factor I of fresh curry fish covered in 5 mm thick picung paste placed in a plastic container at 16 ℃ refrigerator temperature, Factor II fresh curry fish without coated with picung paste placed in a plastic container at 16 ℃, with 6 replications. The results showed control protein content of 6.71%, at a temperature of 16 ℃ for 32 hours; treatment with picung seeds 11.88%, at a temperature of 16 ℃ for 32 hours; etc. Results Analysis of factorial ANOVA test at a time factor has a significance value of 0.01, which means that there is an effect caused by a long time factor of observation. In the treatment factor has a significance value of 0.01 then there is the effect caused by the picung seed factor. Then the interaction between time factor and treatment factor has a significance value of 0.05, so there is an effect caused by the interaction between the time factor and the factor of giving picung seeds. Old picung seeds as an influential natural preservative can increase the shelf life, and be able to maintain the protein levels of fish curisi during the preservation period of 48 hours. Compared with 32 hours of preservative seedless curry fish preservation which experienced total decay and decreased protein content.Keywords: Preservation, old picung seed paste, Protein.ABSTRAKIkan kurisi hasil tangkapan nelayan cukup melimpah, ikan kurisi mengandung protein antara 5 – 20 %, lemak lebih kurang 5 % dan mudah lesis (busuk).Ikan kurisi dimanfaatkan masyarakat nelayan dalam bentuk olahan surimi dan ikan kering (ikan asin). Salahsatualternativpenghambat proses pembusukandenganpengawetan menggunakan biji picung tua (Pangium edule Reinw). Tujuan penelitian ini untuk menganalisa kadar protein ikan kurisi hasil pengawetan menggunakan biji picung tua. Metoda penelitan dilakukan secara eksperimen menggunakan Rancangan Faktorial yaitu Faktor I ikan kurisi segar dilumuri pasta picung setebal 5 mm yang ditempatkan dalam wadah plastikpada suhu kulkas 16 oC, Faktor II ikan kurisi segar tanpa dilumuri pasta picung ditempatkan dalam wadah plastikpada suhu kulkas 16 oC,dengan 6 kali ulangan. Hasil penelitian menunjukkan kadar protein kontrol 6,71%, pada suhu 16 oC selama 32 jam; perlakuan dengan biji picung 11,88%, pada suhu 16 oC selama 32 jam. Hasil Analisis uji ANOVA FAKTORIAL pada faktor waktu memiliki nilai signifikansi 0,01 yang berarti terdapat efek yang ditimbulkan oleh faktor lama waktu penyimapan. Pada faktor perlakuan memiliki nilai signifikansi 0,01 Maka terdapat efek yang ditimbulkan oleh faktor biji picung. Kemudian interaksi antara faktor waktu dan faktor perlakuan memiliki nilai signifikansi 0,05 Maka terdapat efek yang ditimbulkan oleh interaksi antara faktor waktu dan faktor pemberian biji picung. Biji picung tua sebagai pengawet alami berpengaruh mampu meningkatkan lama masa simpan, dan mampu mempertahankan kadar protein ikan kurisi selama masa pengawetan yakni 48 jam. Dibandingkan dengan pengawetan ikan kurisi tanpa biji picung selama 32 jam yang mengalami kebusukan total dan megalami penurunan kadar protein.Kata kunci: Pengawetan, Pasta biji picung tua, Protein